Calcium loss on root canal dentin after Ethylenediaminetetraacetic acid (EDTA) application with different varians - Juni J. Nugroho; Christine A. Rovani; Hermiati Daharuddin; Aries C. Trilaksana; Nurhayaty Natsir; Andi Sumidarti (DiscoverSys Inc., 2019)
Objective: This study aimed to compare calcium loss on root canal dentin before and after EDTA application with different varians and concentration with or without surfactant.Material and Methods: Samples are mandibular premolar teeth single root canal, which is divided into 4 groups: Ethylenediaminetetraacetic Acid (EDTA) gel, cream, solution and negative control. They are decoronated in Cemento-Enamel Junction (CEJ), then prepared with Crown Down Pressureless (CDP) technique and separated bucolingual direction. One side was applied in EDTA according their respective groups and the other side was set as sample before application. Samples before and after application of each group are destructed then subsequently measured for their Ca2+’s amount using Atomic Absorption Spectrophotometry (AAS). Data were collected and analyzed using ANOVA and Tukey Post Hoc test.Results: This showed significant differences between Ca2+ amount in root canal dentin before and after application either on EDTA gel, cream, or solution as well as on negative control group (p<0.05).Conclusion: Application of EDTA solution causes the highest calcium loss compared to EDTA gel and cream.